A review of Microtendipes Kieffer from China (Diptera: Chironomidae) - Qi, Xin; Wang, Xinhua H. (Zootaxa, 2006)
Five new species of Microtendipes Kieffer from China are described and illustrated as males: M. angustus, M. quasicaducus, M. tuberosus, M. yaanensis, and M. zhamensis. In addition, M. britteni (Edwards), M. confines (Meigen), M. pedellus (De Geer), and M. truncatus Kawai and Sasa are recorded from China; the record of M. confines (Meigen) is the first for China. A key to the males of Microtendipes in China is given.